THE DYNAMICS OF DETERMINING MEN AND WOMEN PARTS IN MATTERS OF INHERITANCE: A STUDY OF ISLAMIC LAW - Tarmizi, Tarmizi; Gustika Sandra,; Jumra, Jumra; Sakti Yadi, (Jurnal Diskursus Islam, 2022)
This study aims to understand the dynamics of determining men's and women's parts of inheritance; explore thoughts related to contemporary inheritance formulations and analyze from the perspective of Islamic law. This research is library research with a normative approach (syar'i) in the form of literary analysis relevant to the research object, namely the problem of determining men's and women's parts in the matter of inheritance. The Data were collected structurally through document studies to be analyzed. Data analysis uses qualitative content analysis of relevant documents or texts. As a result, determining men's and women's parts is currently experiencing dynamics 2:1 to 1:1 concept because of the influence of customary law, distribution of inheritance level of welfare, and understanding of the justice value, which has shifted from based on rights and obligations which interpreted according to the needs and conditions. The 1:1 inheritance paradigm or equal share results from the ijtihad of contemporary figures by understanding the value of justice according to social situations and conditions and gender equality. The initiators of the paradigm are Hazairin with the concept of bilateral inheritance, Munawir Sjadzali with his quantitative equation, Muhammad Syahrur, and Yahya Harahap with the concept of boundary theory. According to Islamic law, the 1:1 inheritance paradigm is not contradictory because the goal is for the common good of the heirs. In contrast, the benefit is the goal of Islamic law through the concept of maqāsiḍ sharia by paying attention to the rules of Islamic law, such as not ignoring human rights and maintaining good relations with others. Islamic law, with its flexibility that can adapt to place, time, and circumstances, has also blended with the results of contemporary ijtihad.